Combinatorial optimization technique for improving performance of PV modules under partial shading conditions. (2021) - Viswanathan, Tamilarasu; Mathankumar, M.; Rajaguru, R.; Sasikumar, C.
Abstract: In this work, the development of Photo Voltaic (PV) modules operation under partial shading conditions is attained over and done with combinatorial optimization technique. The different power – voltage peak values attained by means of partial shading in the solar panels. The outcomes of progression significantly disturb the overriding algorithms and cause enormous power depletion in energy gathering. The current algorithms are incompetent to apprehending the difference and performance speedy. Combinatorial optimization has proficient of diverse strengthening and divergence mechanisms with each other (power –voltage). Different performance parameters like voltage current variation, precision, and response time are engaged for interpretation. The simulation conceded out for different partial shading patterns and validated the mathematical concept of the proposed method.